Chronic Oxytocin Administration as a Treatment Against Impaired Leptin Signaling or Leptin Resistance in Obesity - Altirriba, Jordi; Poher, Anne-Laure; Rohner-Jeanrenaud, Françoise (Frontiers in Endocrinology, 2015)
This review summarizes the existing literature on the effects of oxytocin administration in the treatment of obesity in different animal models and in humans, focusing on the central control of food intake, the oxytocin effects on adipose tissue and the relationships between oxytocin and leptin. Oxytocin is a hypothalamic nonapeptide synthetized mainly in the paraventricular and supraoptic nuclei projecting to the pituitary, where it reaches the peripheral circulation, as well as to other brain regions. Moreover, leptin modulates oxytocin levels and activates oxytocin neurons in the hypothalamic paraventricular nucleus, which innervates the nucleus of the solitary tract, partly responsible for the brain-elicited oxytocin effects. Taking into account that oxytocin is located downstream leptin, it was hypothesized that oxytocin treatment would be effective in decreasing body weight in leptin-resistant DIO animals, as well as in those with leptin or with leptin receptor deficiency. Several groups have demonstrated that in such animal models (rats, mice and rhesus monkeys), central or peripheral oxytocin administration decreases body weight, mainly due to a decrease in fat mass, demonstrating that an oxytocin treatment is able to partly overcome leptin deficiency or resistance. Moreover, a pilot clinical study demonstrated the efficiency of oxytocin in the treatment of obesity in human subjects.